Testing Achievement and Proficiency in Chinese Language Learners: The Elementary Chinese Learners and Job Applicants for Chinese Company - Parinyavottichai, Chanyaporn (Journal of Sinology (วารสารจีนวิทยา), 2009)
This paper discusses two types of test utilizing in two testing situations. The first type is criterion-referenced testing. The writer has used it to evaluate Chinese language learning achievements and progress of a group of foreign students enrolled in an elementary Chinese course. The second type is norm-referenced testing. In particular, two proficiency tests are designed for assessing the listening and speaking abilities of applicants who are applying for jobs in a foreign company in China. The writer has also employed the American Council on the Teaching of Foreign Languages (ACTFL) proficiency guidelines as the basis for choosing test formats and for creating test questions.